المناخ التنظيمي وعلاقته بالالتزام التنظيمي - سقني, بلقاسم; عوينات, هاجر (University of Eloued جامعة الوادي, 2023)
الملخص هدفت هذه الدراسة إلى التعرف عن العلاقة بين المناخ التنظيمي والالتزام التنظيمي من خلال دراسة عينة من الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الشهيد حمه لخضر-الوادي-. وقد انطلقت من التساؤل الرئيسي: كيف يساهم المناخ التنظيمي في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية؟ وقد انبثق عن هذا التساؤل الرئيسي ثلاث: تساؤلات فرعية وهي كالاتي: - كيف تساهم القيادة في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الوادي؟ - كيف يساهم الاتصال في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الوادي؟ - كيف تساهم الحوافز في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الوادي؟ وتندرج هذه الدراسة ضمن البحوث الوصفية التحليلية من خلال استخدام المنهج الوصفي،واعتماد أسلوب التحليل الكمي والكيفي للبيانات المتحصل عليها وطالما أن مجتمع الدراسة عددهم قليل لا يتجاوز35 مفردة، وقد تم اختيار العينة القصدية عن طريق أسلوب المسح الشامل، وقد تمثلت أدوات الدراسة في الملاحظة والمقابلة الاستبيان موزع على مجموعة من الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية – بجامعة الوادي- ولقد أسفرت هذه الدراسة على النتائج التالية: - إن المناخ التنظيمي يساهم في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الوادي. وبطبيعة الحال تم التأكيد من تحقيق الفرضيات الفرعية كما يلي. - تساهم القيادة في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الوادي. - يساهم الاتصال في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الوادي. - تساهم الحوافز في خلق الالتزام التنظيمي لدى الموظفين الإداريين بكلية العلوم الاجتماعية والانسانية بجامعة الوادي. Study summary This study was aimed at identifying the relationship between the organizational climate and the organizational commitment by studying a sample of administrative staff of the Faculty of Social and Humanitarian Sciences of the University of Martyr Hameh Lakhdar-Wadi. She began by asking the main question: Does the organizational climate contribute to creating organizational commitment among the administrative staff of the Faculty of Social and Humanitarian Sciences? This key question has emerged three. Sub-questions: - How does leadership contribute to creating organizational commitment among the administrative staff of the Faculty of Social and Humanitarian Sciences of the University of the Valley? - How does communication contribute to the organizational commitment of the administrative staff of the Faculty of Social and Humanitarian Sciences of the University of the Valley? - How do incentives contribute to the organizational commitment of the administrative staff of the Faculty of Social and Humanitarian Sciences of the University of the Valley? This study is part of analytical descriptive research through the use of descriptive curriculum, Adopting quantitative and qualitative analysis of the data obtained and as long as the study community has a small number of 35 individuals, So the comprehensive survey technique, also called the comprehensive survey method for the study community, has been used. The study tools were the interview, observation and questionnaire distributed to a group of administrative staff of the Faculty of Social and Humanitarian Sciences, University of Wadi. This study has yielded the following results: - The organizational climate contributes to the organizational commitment of the administrative staff of the Faculty of Social and Human Sciences of the University of the Valley. Of course, it was emphasized that the sub-hypotheses were achieved as follows. - Leadership contributes to the organizational commitment of the administrative staff of the Faculty of Social and Humanitarian Sciences of the University of the Valley. - Communication contributes to the organizational commitment of the administrative staff of the Faculty of Social and Humanitarian Sciences of the University of the Valley. - Incentives contribute to the organizational commitment of the administrative staff of the Faculty of Social and Humanitarian Sciences of the University of the Valley.
دراسة ميدانية على عينة من الموظفين الإداريين بكلية العلوم الاجتماعية والإنسانية بجامعة الشهيد حمه لخضر -بالوادي-
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: المناخ التنظيمي، le climat organisationnel, Organizational climate; الالتزام التنظيمي، l'engagement organisationnel, organizational commitment